Penanggulangan Penangkapan Ikan secara Ilegal di Perairan Provinsi Aceh - Adwani, Adwani (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2018)
Countermeasure against illegal fishing in Aceh water territory has not yet run effectively as expected in accordance with the Law Number 45 of 2009 on Fisheries. This research aims to identify the policies of the local government relating to the countermeasure of illegal missing the mentioned territory. Data were collected through library research on reliable sources such as books, journals and other scholary works. In addition, field works foe collecting primary data have also been conducted through interview with relevant informen and respondents. It is found that the local government has shown necessary efforts in preventing and combating illegal fishing by issuing regulation concerning fishery issues and making coordination with relevant parties the Navy, Office of Maritime Affairs and Panglima Laot. Nevertheless, more efforts are needed including the issuance of the more specific regulation on illegal fishing which can address the case of illegal fissing by foreign fishing vessels. This is important since the existing regulation can only deal with the case of illegal fishing carried out by local fishermen with regards to illegal fishing gear and fishing permits.